Indigenous Cipatat Kolot Society Resilience Based on Leuit in Bogor, West Java - bahagia Bahagia; Rimun Wibowo; Fachruddin Majeri Mangunjaya (ETNOSIA : Jurnal Etnografi Indonesia, 2020)
The purpose of this research is to investigate the community resilience based on Leuit (traditional storage of paddies) in Cipatat Kolot customary community in Bogor, West Java. The research method exerts an ethnographic qualitative approach. To assemble data, an in-depth interview with the Cipatat Kolot customary community leaders and observation and documentation was used. The primary information sources of the research come from the leaders of Cipatat Kolot. The result is that the Cipatat Kolot community conserves traditional storage, namely leuit as a traditional building to store paddies from disasters like flooding. It can strengthen cultural resilience because storing paddies in leuit is a traditional heritage from their forefather. Directly, the cultural value can be nurtured from vanishing amid environmental and cultural changes, which can encourage people’s resilience. When storing paddies, there are rules like people must keep half of the overall paddy yields in leuit, and a half of paddy yields must be store at home. People can directly adapt to climate, environmental issues, and eco-catastrophe because they have ample staple food in traditional storage and house.